Juxtaposing Parents' and Children's Interests in Choosing Madrasah: The Case of Muslim Minority Families in Bitung, Indonesia - Sulaiman Mappiasse; Morty Tria Adonis; Mohamad S. Rahman; Abdul Muis Vangino Daeng Pawero (IAIN Manado, 2026)
Choosing a school for Muslim children in a minority area is not always a smooth process, as parents often try to find a balance between piety and quality. This article examines how parents and children negotiate the decision to prefer a madrasah over a general school among Muslim families in Bitung, North Sulawesi, a region where Muslims constitute a religious minority. By interviewing parents and students, the study finds that parental decisions to send their children to madrasahs are primarily driven by concerns over preserving their children's religious identity and providing them with moral education. There had also been concern about practical considerations, such as school facilities and quality. Some children, on the other hand, refused their parents' choice mostly because they did not like studying too much religious content or memorizing the Qur'an. However, after attending madrasah, some had positive experiences due to perceived good madrasah programs and environment. These dynamics indicate underlying tensions in educational decision-making. But these tensions were mainly quiet. Finally, we discuss implications for madrasah education in plural contexts where Muslims exist as a minority group